Crystal structure of the dihydrate of tetraethylammonium 1,3,5-thiadiazole-5-amido-2-carbamate, C11H27N5O4S - Tan Xiaoke; Zhu Xin (Zeitschrift für Kristallographie - New Crystal Structures)
C11H27N5O4S, triclinic, P1‾$\overline{1}$ (no. 2), a = 7.8359 (2) Å, b = 8.6966 (3) Å, c = 12.9907(4) Å, α = 92.047 (2)°, β = 92.041 (2)°, γ = 96.087 (2)°, V = 879.02 (5) Å3, Z = 2, Rgt(F) = 0.0412, wRref(F2) = 0.1265, T = 298 K.